Rice hull/MnFe2O4 composite: Preparation, characterization and its rapid microwave-assisted COD removal for organic wastewater - Lv, Shuangshuang; Chen, Xuegang; Ye, Ying; Yin, Suhang; Cheng, Jipeng; Xia, Meisheng (Journal of hazardous materials, 2009)
Adsorbent/ferrite composites can adsorb and degrade organics in the organic wastewater treatment. In this study, a rice hull/MnFe(2)O(4) composite (RHM) was prepared via calcination under nitrogen atmosphere and was used to treat organic wastewater with the assistance of microwave radiation. Rice hull was pyrolysed to a porous substrate that consisted of silica and activated carbon under high temperature. Monodisperse spinel MnFe(2)O(4) nanoparticles whose mean diameter is around 59 nm are distributed on the substrate. With the assistance of microwave radiation, RHM was motivated to a hotspot of adsorption and catalysis which could remove more than 70% COD of wastewater within 6 min. The maximum COD removal was 73.5% when the concentration of RHM was 15 mg mL(-1) and the irradiation time of microwave radiation was 6 min. Although the BET surface area and iodine value of RHM are half of rice hull ash (RHA), the COD removal of RHM is 7-20% higher than that of RHA. It is attributed to the presence of MnFe(2)O(4), which enhances the catalytic activity of RHM. RHM can be regenerated via water washing. However, the surface area and the maximum COD removal of RHM decrease for each regeneration cycle. With the advantages of low cost and rapid processing, this novel rice hull/MnFe(2)O(4) composite could gain promising application in wastewater treating-agent.